Optimized Heat Distributions for Laser-Assisted Forming - Ferdinand Bammer (Journal of Engineering)
Forming is limited for many modern materials due to their brittleness. Recent publications propose therefore partial heating of the forming areas, e.g., with laser technology, however, without asking how to minimize the applied energy. This work discusses such an optimization of the temperature distribution to save energy, to avoid unnecessary changes of the material properties, and to minimize thermally induced deformations. The findings are demonstrated on a statically determined quasi 1D-problem, namely, 3-point-bending, and showed for a certain material law (modelling a dual phase steel of type DP1000) that the concentration of heat on the central line of the forming area is counter-productive and that the necessary energy can be significantly reduced with a well-defined heating strategy. Furthermore, we discuss how to extend the analysis to more complex problems which can be treated only numerically.